PUNK`s NOT DEAD: KAJIAN BENTUKAN BARU BUDAYA PUNK DI INDONESIA - Muhammad Fakhran al Ramadhan (Fakultas Komunikasi, Sastra, dan Bahasa, 2016)
The paper aims to analyze the punk subculture as phenomenon in absorbing to the Indonesian local context. Specifically, the findings of this paper see how the global context influenced forming the new local context of Punk as phenomenon regarding to music and fashion. This paper will explain the new form of Punk in Indonesia